2016
DOI: 10.1097/aud.0000000000000338
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Hearing Aid Management: Parent-Reported Needs for Learning Support

Abstract: Although parents reported overall that their needs for hearing aid education and support had generally been met, there were important suggestions for how audiologists and other service providers could better meet parent needs. Hearing aid use for young children was variable and influenced by a variety of factors. Understanding parent experiences and challenges can help audiologists more effectively focus support. Audiologists are more likely to meet the needs of families if they take care to provide access to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 16 publications
1
46
1
Order By: Relevance
“…Further, children with CIs reported concerns about social and school functioning, according to Haukedal, Lyxell, and Wie (2019), when they were assessed by the generic questionnaire Pediatric Quality of Life Inventory. Finally, studies found benefits in the social competence of children with CIs or HAs (Muñoz et al, 2016;Freeman, Pisoni, Kronenberger, & Castellanos, 2017).…”
Section: Social-emotional and Behavioural Functioningmentioning
confidence: 96%
See 2 more Smart Citations
“…Further, children with CIs reported concerns about social and school functioning, according to Haukedal, Lyxell, and Wie (2019), when they were assessed by the generic questionnaire Pediatric Quality of Life Inventory. Finally, studies found benefits in the social competence of children with CIs or HAs (Muñoz et al, 2016;Freeman, Pisoni, Kronenberger, & Castellanos, 2017).…”
Section: Social-emotional and Behavioural Functioningmentioning
confidence: 96%
“…These significant factors increased the presence of differences between all parents and enhanced their need for practice in inclusive education. No doubt, the variable parents' socioeconomic status is explicitly connected to effective management strategies (i.e., parent-audiologist partnership) that had been demanding in research synthesis (Muñoz et al, 2016).…”
Section: Parents' Perceptions Of Hrqol: Groups Similarities and Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent to which individuals believe they need treatment has also been shown to influence adherence to treatment recommendations (Ross, Walker, & MacLeod, 2004;Weaver & Grusntein, 2008). Parents or caregivers of children with hearing loss are similarly affected by psychological variables that may influence their engagement in treatment (Muñoz et al, 2016). These findings suggest psychological factors affect how much individuals engage in audiological interventions.…”
Section: Measuring Psychological Inflexibility In Adult and Child Heamentioning
confidence: 99%
“…Parents experience varying levels of difficulty, depending on their barriers, managing hearing aid use and monitoring device function. Parents have reported a range of challenges such as, frustration in keeping the hearing aids on their child and a lack of confidence knowing how to manage the hearing aids, and they have indicated that they want more learning support (Muñoz, Preston, and Hicken 2014;Muñoz et al 2016Muñoz et al , 2019. Hours of hearing aid use varies widely among young children, typically falling below recommendations (Muñoz et al 2015;Walker et al 2013;Jones and Launer 2010) with parent report often overestimating hours of use when compared to hearing aid datalogging (Walker et al 2015).…”
mentioning
confidence: 99%